DSC3 expression is regulated by p53, and methylation of DSC3 DNA is a prognostic marker in human colorectal cancer - Tiantian Cui; Y Chen; Linlin Yang; Thomas Knösel; Kristin Zöller; Otmar Huber; Iver Petersen (2011)
Desmocollin 3 (DSC3), a member of the cadherin superfamily and integral component of desmosomes, is involved in carcinogenesis. However, the role of DSC3 in colorectal cancer (CRC) has not yet been established. Desmocollin 3 expression in CRC cell lines was analysed by RT–PCR and western blotting. Methylation status of DSC3 was examined by demethylation tests, methylation-specific PCR, and bisulphite sequencing (BS). The regulatory role of p53 was investigated by transfection. Desmocollin 3 was downregulated in CRC cells at mRNA and protein levels. Desmocollin 3 expression was restored in five out of seven cell lines after 5-aza-2′-deoxycytidine (DAC) treatment. A heterogeneous methylation pattern was detected by BS in promoter region and exon 1 of DSC3. Methylation of DSC3 genomic sequences was found in 41% (41 out of 99) of primary CRC, being associated with poor prognosis (P=0.002). Transfection of p53 alone or in combination of DAC increased the DSC3 expression. Similarly, treatment with p53 inducer adriamycin alone or in combination with DAC enhanced DSC3 expression. DNA methylation contributes to downregulation of DSC3 in CRC cell lines. Methylation status of DSC3 DNA is a prognostic marker for CRC. P53 appears to have an important role in regulating DSC3 expression.